Fault-zone structure and weakening processes in basin-scale reverse faults: The Moonlight Fault Zone, South Island, New Zealand. (October 2016) - Alder, S.; Smith, S.A.F.; Scott, J.M.
Abstract: The >200 km long Moonlight Fault Zone (MFZ) in southern New Zealand was an Oligocene basin-bounding normal fault zone that reactivated in the Miocene as a high-angle reverse fault (present dip angle 65° –75° ). Regional exhumation in the last c. 5 Ma has resulted in deep exposures of the MFZ that present an opportunity to study the structure and deformation processes that were active in a basin-scale reverse fault at basement depths. Syn-rift sediments are preserved only as thin fault-bound slivers. The hanging wall and footwall of the MFZ are mainly greenschist facies quartzofeldspathic schists that have a steeply-dipping (55° –75° ) foliation subparallel to the main fault trace. In more fissile lithologies (e.g. greyschists), hanging-wall deformation occurred by the development of foliation-parallel breccia layers up to a few centimetres thick. Greyschists in the footwall deformed mainly by folding and formation of tabular, foliation-parallel breccias up to 1 m wide. Where the hanging-wall contains more competent lithologies (e.g. greenschist facies metabasite) it is laced with networks of pseudotachylyte that formed parallel to the host rock foliation in a damage zone extending up to 500 m from the main fault trace. The fault core contains an up to 20 m thick sequence of breccias, cataclasites and foliated cataclasites preserving evidence for the progressive development of interconnected networks of (partly authigenic) chlorite and muscovite. Deformation in the fault core occurred by cataclasis of quartz and albite, frictional sliding of chlorite and muscovite grains, and dissolution-precipitation. Combined with published friction and permeability data, our observations suggest that: 1) host rock lithology and anisotropy were the primary controls on the structure of the MFZ at basement depths and 2) high-angle reverse slip was facilitated by the low frictional strength of fault core materials. Restriction of pseudotachylyte networks to the hanging-wall of the MFZ further suggests that the wide, phyllosilicate-rich fault core acted as an efficient hydrological barrier, resulting in a relatively hydrous footwall and fault core but a relatively dry hanging-wall. Highlights: Rare field opportunity to study basin-scale normal fault zone reactivated in compression. Fault zone structure in basement controlled mainly by host rock lithology and anisotropy. Hanging wall laced by networks of steeply-dipping pseudotachylytes. Fault core contains progressively foliated fault rocks rich in chlorite and muscovite. Frictionally weak core facilitated steep reverse faulting and acted as hydrological barrier.